Dose-related alterations of carbon nanoparticles in mammalian cells detected using biospectroscopy: potential for real-world effects - Li, Junyi; Strong, Rebecca; Trevisan, Júlio; Fogarty, Simon W; Fullwood, Nigel J; Jones, Kevin C; Martin, Francis L (Environmental science & technology, 2013)
Nanotechnologies generate a wide range of engineered nanomaterials that enter into our ecosystem, especially carbon-based nanoparticles (CNPs). As these novel materials acquire ever increasing numbers of applications, they may pose a risk to organisms, including humans. However, our knowledge of nanoparticle-induced effects remains limited. We are yet to understand the interaction between nanoparticles and organisms, and classical toxicology fails to provide models for risk assessment. Biospectroscopy techniques were employed to identify the effects induced by real-world levels of a panel of CNPs. MCF-7 cells concentrated in S-phase or G0/G1-phase were treated for 24 h with short or long multiwalled carbon nanotubes (MWCNTs) or Fullerene (C60) at the following concentrations: 0.0025 mg/L, 0.005 mg/L, 0.01 mg/L, 0.025 mg/L, 0.05 mg/L, and 0.1 mg/L. Attenuated total reflection Fourier-transform infrared (ATR-FTIR) spectroscopy coupled with computational analysis was then applied to interrogate the cells and significant dose-related effects were detected. From derived infrared spectra, distinct spectral biomarkers of cell alteration induced by each CNP type were identified. Additionally, Raman spectroscopy was applied and allowed us to determine that reactive oxygen species (ROS) were generated by CNPs. These observations highlight the potential of biospectroscopy techniques to determine CNP-induced alterations in target mammalian cells at ppb levels.